2020
DOI: 10.1128/aac.02542-19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ceftolozane-Tazobactam in Combination with Colistin against Extensively Drug-Resistant Pseudomonas aeruginosa, Including High-Risk Clones, in an In Vitro Pharmacodynamic Model

Abstract: Combination therapy is an attractive therapeutic option for extensively drug-resistant (XDR) Pseudomonas aeruginosa infections. Colistin has been the only treatment available for these infections for many years, but its results are suboptimal. Ceftolozane-tazobactam (C/T) is a newly available therapeutic option that has shown good antipseudomonal activity, even against a number of XDR P. aeruginosa strains. However, data about combinations containing C/T are scarce. The aim of this study was to analyze the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The results suggested collaborative disruption of the cell wall since both colistin and cephalosporins targets strategic components of the cell wall. Ceftazidime-avibactam in combination with colistin was previous reported to be effective against colistin non-susceptible strains of multidrug resistant (MDR) Pseudomonas aeruginosa [ 42 , 43 ]. In addition, combinations of ceftazidime/avibactam and colistin, tobramycin, or tigecycline were effective against OXA-48-producing Enterobacterales strains [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested collaborative disruption of the cell wall since both colistin and cephalosporins targets strategic components of the cell wall. Ceftazidime-avibactam in combination with colistin was previous reported to be effective against colistin non-susceptible strains of multidrug resistant (MDR) Pseudomonas aeruginosa [ 42 , 43 ]. In addition, combinations of ceftazidime/avibactam and colistin, tobramycin, or tigecycline were effective against OXA-48-producing Enterobacterales strains [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 . Bactericidal activity was defined as a reduction of 3 log 10 CFU/mL from the initial bacterial load 23 .
Figure 1 Study flow showing in vitro 10-day HFIM assays conducted with three XDR Pseudomonas aeruginosa ST175 isolates with C/T MICs ranging from 2 to 16 mg/L using different Css of C/T in CI: 20 and 45 mg/L to test the emergence of C/T resistance in the susceptible ST175 (10-023) isolate, and 45 and 80 mg/L to test the effectiveness of C/T against the non-susceptible isolates ST175 (09-012) and ST175 (07-016).
…”
Section: Methodsmentioning
confidence: 99%
“…In an in vitro study aimed to evaluate the antibacterial activity of TOL-TAZ and colistin alone and in combination against a collection of 24 clinical XDR P. aeruginosa, Montero et al demonstrated synergistic or additive effect for TOL-TAZ plus colistin (21/24), including TOL-TAZ-resistant strains [ 7 ]. The same group also evaluated the efficacy of TOL-TAZ in combination with meropenem against XDR strains in a hollow-fiber model.…”
Section: Combination Therapy Against Mdr/xdr P Aeruginosa Strainsmentioning
confidence: 99%